2013
DOI: 10.1111/liv.12252
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide precipitates hepatic encephalopathy and increases blood–brain barrier permeability in mice with acute liver failure

Abstract: These findings represent the first direct evidence of inflammation-related BBB permeability changes in ALF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…2,4 On the other hand, material from ALF animals in which edema and encephalopathy were precipitated by infection manifest clear alterations of both BBB function and of expression of BBB tight junction proteins. 5 These latter findings suggest that, in ALF accompanied by significant infection/inflammation, brain edema may comprise both cytotoxic and vasogenic components.…”
mentioning
confidence: 85%
“…2,4 On the other hand, material from ALF animals in which edema and encephalopathy were precipitated by infection manifest clear alterations of both BBB function and of expression of BBB tight junction proteins. 5 These latter findings suggest that, in ALF accompanied by significant infection/inflammation, brain edema may comprise both cytotoxic and vasogenic components.…”
mentioning
confidence: 85%
“…37 Conversely, others have shown that mice injected with AOM alone do not have increased BBB breakdown alone, but require a priming dose of lipopolysaccharide for the BBB permeability to be evident. 39 Together, these in vivo reports do not support the idea that AOM is directly causing leakiness of the BBB; rather, it is a consequence of liver failure and the resulting complications that arise.…”
Section: The Aom Model Of Acute Liver Failure Is a Valid Model Of Hementioning
confidence: 96%
“…A number of substances such as ammonia, serotonin, bradykinin, adenosine, purine nucleotides, interleukins, free radicals, nitric oxide, and steroids may influence the brain endothelium function and tightness of the BBB [38]. Inflammation-related BBB permeability changes in acute liver failure [39]. Hepatitis C virus (HCV)-related neurocognitive dysfunction has been believed to be a consequence of cirrhosis-associated hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%